PENGARUH JIWA KEWIRAUSAHAAN TERHADAP KEBERHASILAN USAHA CAFE DI KOTA PALEMBANG - Dian Utari; Muhammad Yusrik (JEMBATAN (Jurnal Ekonomi, Manajemen, Bisnis, Auditing, dan Akuntansi), 2021)
Success business is usually influenced by many factors, both from the internal and external environment of the company. Factors from the internal environment usually come from within the company's own environment which tends to be controlled. One of the internal factors of business success is the entrepreneurial spirit factor. This study will discuss "The influence of the entrepreneurial spirit on the success of a cafe business in Palembang City". The formulation of the problem in this study is 1. the influence of the entrepreneurial spirit on the success of the Cafe business in Palembang City partially? 2. The influence of the Entrepreneurial Spirit on the success of the Cafe business in Palembang City simultaneously?. The purposes of this study are 1. To determine the influence of the entrepreneurial spirit on the success of the cafe business in Palembang City partially. 2. To find out the influence of Entrepreneurial Spirit on the success of Cafe Business in Palembang City partially. The object of research in this study were 33 cafe businesses in the city of Palembang which were collected by researchers. This study uses quantitative analysis methods. The number of samples collected was 33 respondents and the sample technique used was purposive sampling. From the results of research and interpretation of data that has been analyzed using multiple analysis shows that 67.3% entrepreneurial spirit which consists of variables of confidence, tasks and results, leadership, leadership, and future development affect the success of the cafe business in the city of Palembang and overall. Simultaneous has a significant positive effect on business success where Fcount is greater than Ftable: 8,929 > 2,42 at 5% significance level and significant value is 0.000. This study also shows that the most dominant dimension influencing the success rate of Cafe business in Palembang is the self-confidence dimension with a regression coefficient of 0.436. To increase the entrepreneurial spirit which will affect the success of the cafe business in the city of Palembang, it is necessary to instill an entrepreneurial spirit. This is done so that the cafe business activists really become entrepreneurs or true entrepreneurs.